1996
DOI: 10.1159/000292270
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans’ Cells and L1 Antigen Expression in Normal and Abnormal Squamous Epithelium of the Cervical Transformation Zone

Abstract: This study evaluates the presence of Langerhans’ cells and expression of L1 antigen in squamous epithelium of the normal and dysplastic transformation zone of the cervix uteri and determines the influence of tobacco smoking and pregnancy. Women who smoked and pregnant women showed a decrease of Langerhans’ cell counts in normal epithelium. In cervical intraepithelial neoplasia (CIN) 1 lesions, decreased Langerhans’ cell counts were noted. L1 antigen expression was significantly less in CIN of all grades. Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
4
6
0
5
Order By: Relevance
“…Our results were similar to others mentioned in the literature [11,13]. It was not the objective of this study to compare the number of cervical epithelium Langerhans cells of healthy women with that of women presenting with CIN 3.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were similar to others mentioned in the literature [11,13]. It was not the objective of this study to compare the number of cervical epithelium Langerhans cells of healthy women with that of women presenting with CIN 3.…”
Section: Discussionsupporting
confidence: 92%
“…30 These effects may result from decreased numbers of Langerhans cells in the cervix of women who smoke. 31 Women who consume alcohol are considered to present a high and progressive risk of developing in situ and invasive cervical and vaginal cancer. Epidemiological data have suggested a direct link between alcoholism and lifestyle factors such as promiscuity, smoking, use of hormonal contraceptives and dietary deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of immunosuppression, recent studies have confirmed that cervical dysplasia develops in those individuals whose immune systems are unable to clear HPV, resulting in persistent infection [4,5]. Among cigarette smokers, a decrease in the numbers of Langerhans' cells and CD4 cells in cervical stroma was demonstrated [6,7], suggesting that the increased risk of dysplasia seen in association with tobacco use may be due, at least in part, from local immune suppression. The regression of early dysplasia, therefore, appears to depend on the ability of the immune system to eradicate virally infected hyperproliferative cells.…”
Section: Introductionmentioning
confidence: 99%